2012
DOI: 10.1021/es300720f
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Eu(III) and Graphene Oxide Nanosheets Investigated by Batch and Extended X-ray Absorption Fine Structure Spectroscopy and by Modeling Techniques

Abstract: The interaction mechanism between Eu(III) and graphene oxide nanosheets (GONS) was investigated by batch and extended X-ray absorption fine structure (EXAFS) spectroscopy and by modeling techniques. The effects of pH, ionic strength, and temperature on Eu(III) adsorption on GONS were evaluated. The results indicated that ionic strength had no effect on Eu(III) adsorption on GONS. The maximum adsorption capacity of Eu(III) on GONS at pH 6.0 and T = 298 K was calculated to be 175.44 mg·g(-1), much higher than an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
228
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 487 publications
(245 citation statements)
references
References 42 publications
13
228
0
4
Order By: Relevance
“…Thus, the lack of an ionic strength effect on Cr(III) adsorption suggested that Cr(III) is adsorbed on GO mainly through the coordination with the O-containing functional groups of GO to form inner-sphere complexes. In previous studies, the adsorption of Eu(III) and Pb(II) on GO were also independence of ionic strength [13,31], which was consistent with the result in this paper. Fig.…”
Section: Effect Of Ph and Ionic Strengthsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, the lack of an ionic strength effect on Cr(III) adsorption suggested that Cr(III) is adsorbed on GO mainly through the coordination with the O-containing functional groups of GO to form inner-sphere complexes. In previous studies, the adsorption of Eu(III) and Pb(II) on GO were also independence of ionic strength [13,31], which was consistent with the result in this paper. Fig.…”
Section: Effect Of Ph and Ionic Strengthsupporting
confidence: 92%
“…[9][10][11]. Among these approaches, adsorption has been found to be superior to other techniques due to its low-cost, high efficiency and easy operation [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…As for GBNs, little information is available regarding the interactions between GBNs and HA, and their subsequent effects on the adsorption of coexisting contaminants. Previous studies usually examined the adsorption of contaminants by GBNs in single solute system [17][18][19][20][21][22]. Results showed that graphene oxide was an effective adsorbent for the removal of heavy metal from water due to the coordination between metal ion and O-containing functional groups of graphene oxide [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 5 showed the FTIR spectra of GO and GO + P. catenlannulatus after naphthalene adsorption. For GO, the peaks at approximately 1725, 1620, 1390, and 1085 cm −1 corresponded to the stretching vibration of the C=O, skeletal C=C, carboxyl O=C-O, and alkoxy C-O bond, respectively [2,25,39,40]. The widen peaks at 3450 cm −1 (data not shown) were assigned to the -OH stretching vibration of adsorbed water [41].…”
Section: Adsorption Mechanismmentioning
confidence: 98%
“…Graphene oxide (GO), as the precursor of graphene, exhibits the large number of hydroxyl and epoxy groups in the plane and a small amount of carboxyl and carbonyl group at the edge [1][2][3]. Recently, it has been reported that GO displays the excellent adsorption performance for many organic contaminants, such as dyes [4][5][6][7], polychlorinated biphenyls (PCBs) [8][9][10], and polycyclic aromatic hydrocarbons (PAHs) [11][12][13].…”
Section: Introductionmentioning
confidence: 99%